Characteristics and mineralisation of platinum-group elements (PGE) in the upper group 2 chromitite (UG2) and merensky reefs at the Buffelshoek farm , Two rivers platinum mine: implications for platinum-group elements recovery - Pheeha, Lesetja Charles. (My University, 2022)
The Two Rivers Platinum Mine (TRP) located in the Eastern Bushveld Igneous Complex is currently exploiting platinum-group elements (PGE) in the Upper Group 2 chromitite (UG2) Reef at the Dwarsrivier Farm. TRP has acquired a new prospect (at the Buffelshoek Farm) and is currently planning to mine the UG2 Reef and potentially also the Merensky Reef (MR). Three drill-cores which intersected the UG2 Reef and MR at the Buffelshoek Farm made available by TRP were sampled for mineralogical studies using complementary techniques including reflected light microscopy, mineral liberation analyser and electron microprobe. The platinum group minerals (PGM) which host the PGE exhibit variability in their flotation rates and consequently variable PGE recoveries that is mostly attributed to the not so well understood PGM distributions and characteristics. The purpose of the study was to investigate the PGE process mineralogical characteristics such as the PGM phases, their modal abundances and mineral associations, as well as the grain size distributions within the UG2 Reef and MR at the Buffelshoek Farm. The observed PGM phases are broadly grouped into PGE sulphides, PGE arsenides, PGE bismuth-tellurides, PGE antimonides and PGE alloys. The PGM phases are largely dominated by PGE-sulphides (average of 80%) in the UG2 Reef and PGE-arsenides (average of 39%) in the MR. Although the UG2 Reef and MR are mineralogically different, the PGM observed are similar in composition, but vary in their proportions. The PGM are mostly associated with base metal sulphides typically, pentlandite in the UG2 Reef and silicates, which are dominated by amphiboles in the MR. The PGM grain sizes generally range between 2 and 22 microns in the UG2 Reef and range between 2 and 32 microns in the MR. The concentrations of platinum are the highest in both the UG2 Reef and MR, and with the platinum largely deported in PGE-sulphides (about 69 - 84.9%) in the UG2 Reef and PGE-arsenides in the MR. Palladium is mostly deported in the PGE sulphides (about 52.3 - 69.2%) in the UG2 Reef and mostly deported in PGE antimonides (about 43%) and PGE bismuth-tellurides (about 37%) in the MR. Rhodium (Rh) is entirely deported in the PGE sulphides in the UG2 Reef and deported in PGE sulphides (about 86.5%) and PGE bismuth-tellurides (about 13.5%) in the MR. Expected recoveries of PGM ranges from 76 to 89% for PGE sulphides and arsenides in the UG2 Reef and 61.3% in the MR, which is considered good. PGE bismuth-tellurides, PGE antimonides and PGE alloys are expected to be variably to poorly recovered, requiring suitable reagents to be well recovered both in the UG2 Reef and MR.
Thesis (M.Sc. (Geology)) -- University of Limpopo, 2022
Keywords: Platinum group elements; Upper group 2 chromitite; Merensky reef; Two rivers platinum mine; Process mineralogy; Platinum group; Abandoned mines; Platinum mines and mining